Retention of Pollutants Elements from Mine Tailings of Lead in Geopolymers for Construction - Terrones Saeta, Juan María; Suárez Macías, Jorge; Castañón García, Ana María; Gómez Fernández, Fernando; Corpas Iglesias, Francisco Antonio (MDPI, 2024)
The construction sector is one of the most demanding sectors of raw materials in existence today. As a consequence, the extraction of these materials has a significant impact on the environment. At the same time, mining activities produce a series of wastes, in some cases with polluting elements, which must be treated to avoid pollution. Therefore, the use of mining waste for the conformation of new construction materials is an important environmental advantage, even more so when such waste is prevented from producing polluting leachates. Therefore, in this research, geopolymers are developed with mine tailings from the Linares lead mines, chemically activated with potassium hydroxide. For this purpose, different percentages of the alkaline activator were tested and the physical and mechanical properties of the conformed materials were evaluated. The analysis of the different conformed geopolymers determined the optimum percentage of potassium hydroxide for conforming the geopolymer with the best mechanical and physical properties. In addition, the concentration in the leachate of potentially contaminating chemical elements in the mining waste was estimated to be lower than those regulated by the regulations. Consequently, this research shows the development of a sustainable material for construction with mining waste and reduction of the environmental impact of traditional products.
Keywords: geopolymer; mining waste; retention of potentially toxic elements; potentially toxic elements; circular economy; sustainability; construction materials